Research hotspots and new trends in the impact of resistance training on aging, bibliometric and visual analysis based on CiteSpace and VOSviewer - Mi, Junmin; Zhang, Litao; Sun, Wei; Wang, Zhen; Yang, Pengbo; Zhang, Jiachen; Zhang, Yani (Frontiers in Public Health, 2023)
Introduction: Resistance training can prevent and treat aging and effectively improve the quality of life of trainees. However, unhealthy living habits such as irregular life, obesity and hyperlipidemia, and chronic diseases lead to a significant decline in the energy level of the population, seriously affecting the health of the population. Our research identifies the research hotspots of resistance training to prevent and treat aging from the perspective of bibliometrics, predicts research frontiers and development trends, and provides more perspectives for research on aging populations. Methods: Use CiteSpace and VOSviewer visualization software to draw the scientific knowledge map of countries/regions, institutions, authors, co-occurrence keywords and co-cited references of published papers, explore the Web of Science core collection database all about resistance training prevention and treatment Research status, hotspots, frontiers and development trends of papers on aging. Results: Among the 760 papers that meet the inclusion criteria, the number of papers published and the frequency of citations have increased steadily in the past five years. Judging from the countries/regions, institutions, scholars, and journals that published papers, the ones with the largest number are USA, Univ Estadual Londrina, Cyrino ES, and Exp Gerontol. The ones with the highest influence are England, Univ Arkansas Med Sci, Frontera WR, Biochem The top five co-occurrence keywords of Bioph Res Co. include exercise, strength, resistance training, skeletal muscle, and muscle strength. The research frontier is physical function. Conclusion: In the field of resistance training treatment and prevention of aging research: relevant scholars deserve further in-depth research and exploration. The United States, Brazil, Canada and other economically developed countries/regions, institutions and authors have greater influence and productivity. These quantitative research results can provide references for relevant scholars' follow-up research and government departments to formulate and modify health policies or measures.